2013
DOI: 10.1353/hpu.2013.0065
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Care for Cambodian Patients with Diabetes: Results from a Qualitative Study

Abstract: Racial and ethnic disparities in diabetes care have been well documented. While root causes have been explored for some minority groups, less is known about smaller immigrant populations such as Cambodians. In this study, we sought to explore the potential barriers to care for Cambodian patients with diabetes. We conducted five focus groups with three study groups: health care providers, bilingual Khmer frontline staff, and Cambodian patients with diabetes. Focus groups findings revealed that certain cultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 73 publications
1
51
0
Order By: Relevance
“…Social workers should advocate to legislators for a significant investment of resources to support CHWs, which would ensure that the right to access health care for some of the most vulnerable and marginalized Americans is realized, that the health care they receive is culturally appropriate, and that they receive preventive care services (Nguyen et al, 2008;Renfrew et al, 2013;Taylor et al, 2013). Employing CHWs would also ensure that health providers are in compliance with Title VI (Berthold & Fischman, 2014;Wagner et al, 2013).…”
Section: Implications For Social Work Practicementioning
confidence: 99%
“…Social workers should advocate to legislators for a significant investment of resources to support CHWs, which would ensure that the right to access health care for some of the most vulnerable and marginalized Americans is realized, that the health care they receive is culturally appropriate, and that they receive preventive care services (Nguyen et al, 2008;Renfrew et al, 2013;Taylor et al, 2013). Employing CHWs would also ensure that health providers are in compliance with Title VI (Berthold & Fischman, 2014;Wagner et al, 2013).…”
Section: Implications For Social Work Practicementioning
confidence: 99%
“…This barrier was identified in 12 of the 28 articles. 12,13,16,20,21,[27][28][29][30]32,35,36 I. Disease and illness experience a) Fears/feelings as barriers to self-management i.…”
Section: Identified Barriers To Carementioning
confidence: 99%
“…Fear or distress: The identified fear could be non-specific, such as fear of loss of control over their life, [14][15][16][17][18][19]37 or of potential future events (disease complications, 14,[22][23][24] and drug side effects 16,19,20,25,35,39 ). The fear could also be specific to events, such as glucose monitoring, 19,20,36 diagnosis, 18,21,22,24,29,37 starting oral medications, 16,18,19,36 starting insulin (including fear of insulin and needles), 16,[18][19][20][21]35,36,39 and fear of hypoglycaemia. 13,16,19 ii.…”
Section: Identified Barriers To Carementioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that Cambodian American CHWs decrease the fragmentation of healthcare, decrease overall healthcare costs and improve health outcomes across a diverse range of health conditions, such as cancer, diabetes and Hepatitis B (California Health Workforce Alliance, ; Nguyen, Tanjasiri, Kagawa‐Singer, Tran, & Foo, ; Renfrew et al, ; Taylor, Bastani, et al, ; Taylor, Burke, et al, ); however, their ability to build and strengthen their communities’ capacity remains understudied. Cambodian American CHWs’ understanding of their communities’ lived experiences and what is most needed at the community level are essential to ameliorating their communities’ health status.…”
Section: Introductionmentioning
confidence: 99%